Meningkatkan Kemampuan Berhitung Anak Usia Dini Melalui Media Puzzle Angka Di PAUD Al-Maghfiroh Sei Kepayang Timur Kabupaten Asahan - Damayanti, Nurainun (Ability: Journal of Education and Social Analysis, 2021)
This research is motivated by the low numeracy skills of children in PAUD Al Maghfiroh Sei Kepayang Timur Kab. sharpen. This is due to the lack of educational game tools that support the learning process. The use of educational game tools in learning aims to train children's concentration, teach quickly, arouse children's emotions and improve children's memory. Number Puzzle Media is an educational game tool. The use of Number Puzzle media is very effective in improving children's numeracy skills. Besides being liked by children, Number Puzzle media is also a fun game media, thus increasing children's motivation in learning to count or mention numbers. The method used in this research is Classroom Action Research (CAR), namely action research carried out with the aim of improving the quality of learning in the classroom. This research is from pre cycle, cycle I and cycle II. Each cycle consists of four stages, namely planning, action, observation and reflection. The subjects of this study were children of group A PAUD Al Maghfiroh with a total of 25 children. Based on the results of the study, it is known that through learning by using Number Puzzle media, it can improve children's numeracy skills. This increase can be seen from the average increase in percent. The increase was before the use of media puzzle Figures 17.3%, after the implementation of the first cycle the average increased to 53.3% and the second cycle increased again to 82.6%. Children's cognitive development will develop well, if parents and teachers can stimulate the development and abilities of children. The use of Number Puzzle media used by teachers in improving children's numeracy skills at Al Maghfiroh PAUD is a very effective medium, making children more responsive and happy in learning to count, so children don't get bored quickly in participating in learning.